Impact of Green Energy on Commodity Producing Sector in Developing Countries - Sania Batool,; Junaid Ul Hassan,; Dr. Farrukh Bashir,; Muhammad Waseem Arshad,; Dr Yousaf Khan, (Dialogue Social Science Review (DSSR), 2025)
This study investigates the impact of green energy on commodity producing sector in developing countries using the panel data from 2000 to 2022. Industry construction was taken as an outcome variable whereas Renewable energy was taken as the main focused explanatory variable along with control variables labor force, Gross capital formation, General government expenditure, GDP per capita and Co2 emission. For data analysis, panel unit root tests, panel ARDL model and causality tests were applied on a data. The ARDL model long run results showed that the main focused variable, Renewable energy positively impacted industry construction followed by Gross fixed capital formation whereas, General government expenditure, Labore force, Co2 emission, GDP per capita, were positively affected the industry construction in developing countries. It was proved that the Renewable energy impedes industry construction so these countries need special considerations.